Analisis Hukum Mengenai Pembunuhan Yang Dilakukan Oleh Penderita Gangguan Jiwa Kategori Skizofreniaparanoid (Studi Putusan Nomor 288/PID.B/2020/PN PMS) - Willyam Siahaan; Ediwarman Ediwarman; Marlina Marlina; M Ekaputra (Jurnal Pencerah Bangsa, 2024)
This research aims to know and analyze about criminal liability of criminals with schizophrenia within Decision of Pematang Siantar District Court Number: 288/PID.B/2020/PN PMS. Next The panel of judges considers is with description defendant and description witnesses as well as tool proof submitted letter by prosecutor Prosecutor General and with existence goods proof results inspection local , whether defendant could to blame or no . As is known in case this is the judge for rule out tool proof description witness and tool proof description expert . So that defendant Suheri Sihombing declared guilty on act criminal The murder he did to victim Vecky Erwanto Damanik . Writing this use method writing normative based on approach Constitution and ingredient law other . Conclusion from writing this is a person who has disease or disturbance soul no always said no capable responsible but must conducted inspection more first , with thereby besides Judge role, role a psychiatrist also very required